SYSTEME MATRILINEAIRE, CONFLITS FONCIERS INTRAFAMILIAUX ET MUTATIONS SOCIALES CHEZ LES AGNI SANWI DE COTED’IVOIRE: ANTHROPOLOGIE DES RECOMPOSITIONS EN COURS - Hervé, Coulibaly Gninlnan (European Scientific Journal, ESJ, 2015)
The matrilinear Agni’s society mainly agricultural, is an essential provider in the national economy of Côte-d’Ivoire. The development of the perennial cultures in this dynastic space however contributed to recompose by a resurgence of conflicts, the order of interaction within the family’s institution, at the basis of structuration of the global existence mode. This internal dynamism in the domestic unit therefore impacts the rest of society in a process of social change.